In silico analysis of ventricular action potential with a current–voltage‐time representation: Thresholds, membrane resistance, repolarization reserve - Massimiliano Zaniboni (Physiological Reports)
Abstract The waveform of ventricular action potential (AP) is a key determinant of the cardiac cycle, a marker of beating pathophysiology, and a target for anti‐arrhythmic drug design. The information contained in the waveform, though, is limited to the actual dynamics of the AP under consideration. By measuring quasi‐instantaneous current–voltage relationships during repolarization, I propose a three‐dimensional representation of the ventricular AP which includes potential dynamic responses that the beat can show when electrically perturbed. This representation is described in the case of a numerically reconstructed ventricular AP, but it can be, at least partially, derived in real cardiomyocytes. Simulation allows to disclose the potentialities and the limitations of the approach, that can be extended to any non‐cardiac AP. By reporting, at any AP time, the ion current available within the physiological membrane potential range at that time, the representation makes all together available: (1) refractory period, (2) thresholds for eliciting full or calcium‐driven APs, (3) threshold for all‐or‐none repolarization, (4) membrane resistance during repolarization, (5) the safety of membrane repolarization. It provides further evidence of a negative membrane resistance during the late phase of ventricular AP and a quantitative estimate of repolarization reserve (RR), key determinants of repolarization dynamics.